Decision Support System for Major Selection in Higher Education for Multimedia Graduate Students using Fuzzy Mamdani Logic - Fauziah, Khasna Nur; Arifin, Fatchul (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
Students at the vocational high school level are indeed prepared to be able to work directly, but it does not rule out the possibility that vocational high school students can continue higher education such as universities. But the problem that will be faced again if students who graduate from vocational high schools choose to continue their education in college is what major they will take. One of the vocational high school majors, namely Multimedia, has a wide scope, so grade 3 vocational high school students who want to go to college have a dilemma in deciding on a major. This research applies the fuzzy logic mamdani to help make decisions for majors in higher education. This study is based on 5 input parameters, namely Komputer dan Jaringan Dasar, Desain Grafis Percetakan, Dasar Desain Grafis, Teknik Audio Visual, and Animasi. There are outputs of 5 majors in Teknik Komputer, Desain Komunikasi Visual, Animasi, TV dan Film, and Fotografi. The results of this research can make it easier and can provide support for grade 3 vocational high school students, especially the Multimedia department in choosing a major in higher education. The results of the decision support system with the highest student score data in Animasi will appear a recommendation score of 79.8 in the Animasi department, and on the highest student score data on the Komputer dan Jaringan Dasar, a recommendation score of 79.8 will appear in the Teknik Komputer major in accordance with the major taken and lived by the current student.